Millennium BCP in the african markets - Salvado, Catarina Soares (2015)
This master thesis is presented in the form of a case study and portrays the internationalization of a Portuguese company, Millennium bcp, to the emerging African markets (Mozambique and Angola), highlighting the main challenges and the strategic options applied in each of them. Millennium bcp is the biggest private bank in Portugal that has soon decided to expand its operations to Angola and Mozambique. It first moved to Mozambique with the brand Millennium Bim and only some years later to the Angolan market with Millennium Angola. While Bim soon got positive results, achieving a leadership position in the Mozambique market and now tries at all costs to preserve it; Millennium Angola has a more reduced presence in the Angolan market and couldn’t achieve the strong desired positioning yet, taking its CEO to a dilemma situation. The present case study should be used as a teaching tool, since it allows the analysis and further discussion, using strategic frameworks that are taught in class, of a real life situation.